O Papel da Pastoral Carcerária, como órgão de monitoramento externo, na prevenção à tortura nos presídios da Paraíba - Silva, Bartolomeu Ferreira da (2009)
Torture in Brazil is a procedure widely used by police and prison staff in places of detention, prisoners against the descendants of the poorest parts of the population and are the merits of the torturers torturers in a situation of physical inferiority and psicológica.remonta ancient historical periods, succeeding generations and deploying the terror victims. It is used as a means of investigation, to boot confession of the victim, and as punishment against a suspect or criminal. Although there is extensive legislation (treaties, conventions, etc..) Prohibiting torture, the same can not be said with the law, since it is a crime that goes unpunished in the Brazilian reality. Intensified during the military dictatorship, persists even in spite of democracy and the Constitution of 1988. Thus does the need to combat the crime of torture strictly through preventive quoting the external monitoring of penal institutions in order to intimidate the tormentors, denouncing them. Who creates a system of regular visits to detention facilities is the Optional Protocol to the Convention against Torture, so that they are carried out unannounced visits and regularly. The aim of this study is to analyze visits to detention centers for Prison Pastoral da Paraíba, in order to prevent torture, to make recommendations to the authorities to improve prison conditions, denouncing injustice etc. In Paraíba, this work takes place in all jails in Joao Pessoa, and the main cities, as Guarabira, Campina Grande, Patos etc. However, the visits are conducted with prior notice. So it is up to Brazil to ratify the Optional Protocol and to defend the designation of the Prison Ministry as the national preventive mechanism for its tradition in visits to penal institutions, their functional independence and political organization, etc...